The Substance of Truth - Olorunda, Tolu. (Transgressions, Cultural Studies and Education ,, 2011)
Tolu Olorunda is a cultural critic whose work has regularly appeared on AlterNet, Black Commentator, CounterPunch, Truthout, and several other publications including ColorLines magazine, The Nation magazine, and Wiretap magazine. His book, The Substance of Truth, takes a frank look into what has become of a society that touts grand and lofty ideals which it often fails to fulfill. With essays addressing issues as broad as the education system, 21st century media culture, Hip-Hop culture, youth culture, neoliberalism, and moral poverty, Olorunda argues the days ahead would darken in promise if rigorous action isn’t soon applied to rectify the way people think, how they respond to their surroundings, and the decisions they take to make the world better than it stands today. This struggle, he insists, could define whether or not a livable future would exist for the most vulnerable of all—children, whose plights are increasingly cast aside and ignored. From the book: “At risk of appearing alarmist, it’s easy to ignore all the warning signs hanging around us that suggest the clock is ticking fast—real fast!—and that time left for due action is short. But if life for the next generation should contain some semblance of sanity—where life itself means more than shopping malls and commodities, where Power stands accountable to the demands of communities—all fear of coming across hyperbolic would have to give way to the realities staring us down. The risk also extends to coming across Pollyannaish, as though all the impurities and iniquities holding hostage society can be cured with essays or lectures. But we cannot afford to let this moment slip by unattended, unengaged. The problems number endless—and so do the possibilities. And at no other moment has a generation been more fortunate, with the ease of technology, to make miracles happen amidst frightening circumstances. At no other moment has the clarion call blared this clearly and loudly.”.